2011
DOI: 10.1007/s10897-011-9374-9
|View full text |Cite
|
Sign up to set email alerts
|

Media Coverage of Direct‐to‐Consumer Genetic Testing

Abstract: Media coverage of Direct-to-Consumer (DTC) genetic testing shapes public perception of such testing. The purpose of this study was to determine and assess the themes presented by U.S. news media regarding DTC genetic testing. We performed a Lexis-Nexis search with the keywords "Direct-to-Consumer" and "genetic test" for news stories published from 2006-2009. The sample was coded on themes of genetic determinism, privacy, discrimination, validity, regulation, the Genetic Information Nondiscrimination Act (GINA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Most investigations focus on awareness of DTC genetic tests, reported intention to order a test, and reasons for why (or not) an individual would purchase one. Although the evidence is limited, and compromised by a lack of representative samples and inconsistency of methods and measures across studies, results thus far suggest that awareness and actual use of DTC testing is relatively low despite emerging mainstream media on the topic (Lynch et al, 2011). In Australia over the last 10 years, there has been considerable mainstream media coverage on genetic testing and genetics and health issues, with specific stories on DTC beginning to emerge in 2003 and peaking in 2007 and 2011 (see Figure 1).…”
Section: Lack Of Research On Public Attitudes Towards Dtc Genetic Testsmentioning
confidence: 99%
“…Most investigations focus on awareness of DTC genetic tests, reported intention to order a test, and reasons for why (or not) an individual would purchase one. Although the evidence is limited, and compromised by a lack of representative samples and inconsistency of methods and measures across studies, results thus far suggest that awareness and actual use of DTC testing is relatively low despite emerging mainstream media on the topic (Lynch et al, 2011). In Australia over the last 10 years, there has been considerable mainstream media coverage on genetic testing and genetics and health issues, with specific stories on DTC beginning to emerge in 2003 and peaking in 2007 and 2011 (see Figure 1).…”
Section: Lack Of Research On Public Attitudes Towards Dtc Genetic Testsmentioning
confidence: 99%
“…In terms of genetics in the media, one of the most recurrent concerns is promotion of genetic determinism [34]. Not all analyses, however, have supported this concern [35,36], and some researchers have suggested that genetic determinism in the news media actually may be decreasing over time [37]. What is found more consistently, particularly in stories on the medical and forensic applications of genetics, is overstatement of the potential of genetic technology that may lead to unrealistic public expectations (termed ''genetic optimism'' by Conrad) [38][39][40].…”
Section: Influence Of the Media As A Common Source Of Informationmentioning
confidence: 99%
“…DTC genetic tests may also be an attractive option to consumers who are concerned about genetic discrimination and confi dentiality. Because DTC occurs outside of a health care provider' s offi ce, genetic test results are not automatically part of medical record, however, concerns have been raised about how DTC companies will keep records confi dential (Lynch, Parrott, Hopkin, & Myers, 2011). Finally, the advertisement of DTC tests for genetic conditions could raise public awareness and knowledge about genetic tests and empower consumers to be better advocates for their health care (Bloss et al, 2010;Farkas & Holland, 2009).…”
Section: Direct-to-consumer Marketing Movementmentioning
confidence: 99%